IMPACT OF EXPLICIT SCIENTIFIC INQUIRY INSTRUCTION HYBRID MODE WITH SOCIOSCIENTIFIC ISSUE CONTEXT ON STUDENTS’ CRITICAL THINKING SKILLS IN CHEMICAL KINETICS - Eli Khusmawardani; Muntholib muntholib; Yahmin yahmin (JCER (Journal of Chemistry Education Research), 2022)
This study aimed to explore whether Explicit Scientific Inquiry Instruction (ESII) Hybrid Mode in the context of Socioscientific Issues could improve the students' critical thinking skills. The research design was a one group pretest-posttest design. The research sample was 31 science eleventh graders at SMA Mojosari for the academic year 2021/2022. The data was collected using a critical thinking skills test on Chemical Kinetics which consists of 27 valid questions with a Cronbach Alpha reliability of 0.756. A paired-samples t-test showed that the Explicit Scientific Inquiry Instruction (ESII) Hybrid Mode in the Socioscientific Issues context improved students’ critical thinking skills (p = 0.00 < 0.05). The improvement was strong as its N-gain score was 0.58 (upper–medium category) and d-effect size was 1.40 (much larger than typical category). This shows that statistically ESII hybrid mode in the context of SSI can improve students' critical thinking skills. Therefore, this strategy can improve students' critical thinking skills in the instruction that allows students to interpret, analyze, explain, evaluate, and draw conclusions